PERANCANGAN SISTEM INFORMASI E-COMMERCE DI TOKO AMALIA BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Dewi, Septi Amaliah; Utomo , Agus Prasetyo (MEANS (Media Informasi Analisa dan Sistem), 2022)
Nowadays, selling online is very popular, because you don't have to go to the store directly for buying and selling transactions. Buying and selling via the internet is called an online shop. Amalia Store is an offline store with no online facilities where buyers are only from those around the store. The author makes an e-commerce design for this store so that it can compete in a wider area. By building an e-commerce website for an online store at the Amalia store, it will bring sales profits because it expands the sales area and adds buyers from various regions. Shopping online is now very easy to do, because with the internet, buyers can shop anywhere and anytime. This convenience makes the online shop very popular in all circles. Analysis of the current system is described using activity diagrams and an explanation of the process that will be designed using use case diagrams. The system design is carried out, using a Class Diagram. From the analysis and design carried out, it will produce an e-commerce information system design on a web-based Amalia store that uses the waterfall method and can be implemented to help manage data and reduce user errors.